Biomarkers associated with 30-day readmission and mortality after pediatric congenital heart surgery - Parker, Devin M. (J Card Surg, 2019)
OBJECTIVES: Novel cardiac biomarkers serum ST2 and Galectin-3 may be associated with increased likelihood of important events after cardiac surgery. Our objective was to explore the association between pre- and post-operative serum biomarker levels and 30-day readmission or mortality for pediatric patients. METHODS: We prospectively enrolled pediatric patients <18 years of age who underwent at least one cardiac surgical operation at Johns Hopkins Children’s Center from 2010 to 2014 (N=162). Blood samples were collected immediately prior to surgery and at the end of bypass. We evaluated the association between pre- and post-operative Galectin-3 and ST2 with 30-day readmission or mortality, using backwards stepwise logistic regression, adjusting for covariates based on the Society of Thoracic Surgeons (STS) Congenital Heart Surgery Mortality Risk Model. RESULTS: In our cohort, 21 (12.9%) patients experienced readmission or mortality 30-days from discharge. Before adjustment, preoperative ST2 terciles demonstrated a strong association with readmission and/or mortality after surgery (OR: 2.58; 95 % CI: 1.17 – 3.66 and OR: 4.37; 95% CI: 1.31 – 14.57). After adjustment for covariates based on the STS congenital risk model, Galectin-3 postoperative mid-tercile was significantly associated with 30-day readmission or mortality (OR: 6.17; 95% CI: 1.50 – 25.43) as was the highest tercile of postoperative ST2 (OR: 4.98; 95% CI: 1.06 – 23.32). CONCLUSIONS: Elevated pre-and postoperative levels of ST2 and Galectin-3 are associated with increased risk of readmission or mortality after pediatric heart surgery. These clinically available biomarkers can be used for improved risk stratification and may guide improved patient care management.